Antimicrobial prescribing for children in primary care. (24th July 2018) - Yan, Jennifer; Hawes, Lesley; Turner, Lyle; Mazza, Danielle; Pearce, Christopher; Buttery, Jim
Abstract : Aim: To describe the patterns of antimicrobial prescribing in general practice for children aged ≤18 years. Methods: This is a review of routinely collected patient data extracted from computerised medical records from 39 general practices in eastern metropolitan Melbourne over a 5‐year period, 2010–2014. Main outcome measures: Proportion of paediatric consultations resulting in antibiotic prescription, type and frequency of antibiotics prescribed, antibiotic prescribing stratified by age, reason for indication and inter‐practice variation. Results: There were 744 883 consultations for 89 983 individual paediatric patients and 85 913 prescriptions for antibiotics during the study period. Of these antibiotic prescriptions, 75 410 were associated with a consultation, and 10 503 (12.2% of all prescriptions) had no associated consultation in the data. On average, one in five individual children was prescribed an antibiotic each year. The most commonly prescribed antibiotics were cephalexin, amoxycillin/clavulanate, cefaclor, phenoxymethylpenicillin and roxithromycin. Less than 3% of all prescriptions were for amoxycillin. Prescribing of cefaclor and roxithromycin decreased, although cefaclor remained the third most common antibiotic choice for general practitioners. Peaks in prescribing were noted over winter months. Reason for prescription was not recorded for 82% of prescriptions. The frequency of antibiotic prescription per consultation varied substantially (2.1–19.7%) between general practitioner clinics. Overall, antibiotic prescribing decreased by 2.3% over the 5‐year period. Conclusions: This study provides a focused examination of antibiotic prescribing practices for children in Australian general practice. More information is required to better understand specific prescribing practices in children, including the low frequency of amoxycillin prescription and ongoing prescription of cefaclor.